2014
DOI: 10.1136/annrheumdis-2014-eular.3210
|View full text |Cite
|
Sign up to set email alerts
|

THU0242 Vx-509 (DECERNOTINIB) Treatment Reduces Levels of Markers for Immune Activation, Bone Degradation and Inflammation but not Interferon Signaling in Patients with Rheumatoid Arthritis

Abstract: Background Janus kinase 3 (JAK3) plays a critical role in gamma-chain cytokine signal transduction and is essential for activation of lymphocytes. Interferon signaling is dependent on other Janus kinase family members, but not JAK3, and is an important component of immune response to infectious agents. VX-509 selectively inhibits JAK3 and improves signs and symptoms in patients with rheumatoid arthritis (RA). Objectives To evaluate the in-vivo pharmacodynamic effects of VX-509 treatment on systemic markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Phase IIa trial demonstrated that twice a day doses of decernotinib (50–150 mg) as monotherapy improves the signs and symptoms of RA and reduces the expression of genes induced by ɣc cytokines (Farmer et al, 2015; Fleischmann et al, 2015; Hare et al, 2014). A Phase II clinical trial in RA was also interesting, where all tested doses of decernotinib (50, 100 or 200 mg once daily (q.d.)…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…Phase IIa trial demonstrated that twice a day doses of decernotinib (50–150 mg) as monotherapy improves the signs and symptoms of RA and reduces the expression of genes induced by ɣc cytokines (Farmer et al, 2015; Fleischmann et al, 2015; Hare et al, 2014). A Phase II clinical trial in RA was also interesting, where all tested doses of decernotinib (50, 100 or 200 mg once daily (q.d.)…”
Section: Clinical Developmentsmentioning
confidence: 99%